Biodiesel production from microalgae Botryococcus braunii - Sriamini sriamini; Rini Susilowati (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2010)
Increasing energy needs cause diminishing energy resources. This encourages the searchfor renewable energy sources to anticipate scarcity. One of the new energy source is microalgae.Microalgae have a high variation of species and have a great potential to be developed as foodand other chemical products. Microalgae has been developed as a potential source of biodieselto replace petroleum fuels derived from foss ils. Of several microalgae s pecies studied,Botryococcus braunii produces the largest oil content, i.e. 75% dry weight. This paper describessteps of producing oil from B. brauniiwhich includes preparation of microalgae biomass,biomass harvesting, and extraction of oil. Oil content of B. braunii is composed mostly ofhydrocarbons (± 15–76% by dry weight), called botryococcene. This type of hydrocarbon ispotential as an energy source of biodiesel.